Ruptura e Legado: o colapso da cordialidade oficial entre o Brasil e a Argentina - Spektor, Matias (2002)
This work aims at identifying which factors lay behind the sudden change in ArgentineBrazilian relations in the early 1980s, when their foreign policies converged into an innovative integration project. The argument put forward is that convergence between the two countries was the unintended legacy of their bilateral interaction during President Geisel’s administration (1974-1979).